How is table tennis in China successful? - Zhang, H.; Zhou, Z. (German Journal of Exercise and Sport Research, 2019)
The Chinese Table Tennis Team, founded in 1952, has won 230 gold medals in the world`s three major competitions (the Olympic Games, World Championships, and World Cup) and has made world-renowned achievements over the last 60 years. This paper explains the reasons for the success of Chinese table tennis from the perspectives of society, training and competition, as well as scientific research: (1) Due to historical reasons, China has chosen to focus on the development of the sport table tennis. Furthermore, table tennis has made important contributions to the development of Chinese society (for example, ping-pong diplomacy), which has given table tennis a special social status in China. (2) China has established an effective three-level training system, league system and coach system, and, through long-term training and competitions, the country has developed an effective method of technical and tactical training and preparation for world competitions. (3) With the assistance of scientific research, Chinese table tennis coaches and players can master the basic rules of table tennis, which is one of the important reasons for the success of Chinese table tennis. Die chinesische Tischtennismannschaft wurde 1952 gegründet. Sie hat in den drei weltweit bedeutendsten Wettbewerben (Olympische Spiele, Weltmeisterschaft und Weltcup) 230 Goldmedaillen gewonnen und über die vergangenen 60 Jahre Errungenschaften von Weltrang vorzuweisen. Im vorliegenden Beitrag werden die Gründe für den Erfolg von Tischtennis in China aus dem Blickwinkel von Gesellschaft, Training und Wettkampf wie auch aus der Perspektive der Forschung dargelegt: 1. Aus historischen Gründen fiel in China die Entscheidung, sich auf die Entwicklung der Sportart Tischtennis zu konzentrieren. Tischtennis hat erheblich zur Entwicklung der chinesischen Gesellschaft beigetragen (Beispiel Pingpong-Diplomatie), was dem Sport in China einen sozialen Sonderstatus eingebracht hat. 2. China hat ein wirkungsvolles dreistufiges Trainingssystem, Ligasystem und Trainersystem geschaffen. Darüber hinaus wurde durch langfristiges Training und Wettkämpfe eine effektive Methode des technischen und taktischen Trainings sowie der Vorbereitung für Wettkämpfe auf Weltniveau entwickelt. 3. Mit wissenschaftlicher Unterstützung schaffen es chinesische Tischtennistrainer und -spieler, die Grundregeln des Sports zu beherrschen, was einer der wichtigsten Gründe für den Erfolg von Tischtennis in China ist.